Frankie [videorecording (DVD)]. - Huppert, Isabelle; Gleeson, Brendan; Tomei, Marisa; Kinnear, Greg, 1963- (Sony Pictures, 2020)
Unfolding over the course of a late summer's day in the fabled resort town of Sintra, Portugal, this film follows three generations who have gathered for a vacation organized by the family matriarch. In this fairy tale setting, husbands and wives, parents and children, friends and lovers, stirred by their romantic impulses, discover the cracks between them, as well as the unexpected depth of feeling.